Gender Differences in Narrative Essay Writing Ability among Indonesian EFL Undergraduate Students - Bayusri, Elina; Pohan, Erwin; Nopita, Dewi (J-LELC: Journal of Language Education, Linguistics, and Culture, 2026)
The research of this study was to determine whether the narrative essay writing abilities of male and female fourth-semester students in the English Language Education Study Program differed noticeably. The study adopted a descriptive comparative quantitative design. A total of 18 students from Class K1 at Raja Ali Haji Maritime University took part, comprising 9 males and 9 females chosen via purposive sampling. To collect the necessary data, participants completed a writing test requiring them to produce a 450-word narrative essay on a shared topic under uniform conditions. Two raters then assessed the essays independently, applying an analytic scoring rubric adopted from Jacobs et al. (1981) that covers five writing dimensions content, organization, vocabulary, language use, and mechanics. Each student's final score represented the average of the two raters' evaluations. The researchers analyzed the data using several statistical procedures: descriptive statistics, the independent samples t-test, Cohen's d to gauge effect size, Levene's test for homogeneity of variance, and Shapiro-Wilk test for normality. Results indicated that female participants scored higher on average (84.11) than their male counterparts (72.89). With a two-sided p-value of 0.033 below the 0.05 threshold the t-test confirmed a statistically significant gender-based difference in narrative essay writing performance. The effect size, measured at 1.10 using Cohen's d, further indicated a substantial (large) practical distinction between the two groups. When combined, these findings indicate that female students in this sample were better at writing narrative essays than male students.